On the Difference Between Conditional and Unconditional Asymptotic Distributions of Estimates in Distributed Lag Models with Integer-Valued Parameters - Schmidt, Peter (Econometrica, 1973)
Peter Schmidt, On the Difference Between Conditional and Unconditional Asymptotic Distributions of Estimates in Distributed Lag Models with Integer-Valued Parameters, Econometrica, Vol. 41, No. 1 (Jan., 1973), pp. 165-169